Evaluating the Effectiveness of Iron Chelates in Managing Iron Deficiency Chlorosis in Grain Sorghum - A. Obour; R. Perumal (Kansas Agricultural Experiment Station Research Reports, 2015)
Grain sorghum production in alkaline or calcareous soils is frequently affected by iron (Fe) chlorosis. Soil conditions such as high pH, high free calcium carbonate (lime), and low organic matter favor development of iron deficiency chlorosis (IDC), which can delay crop maturity and reduce yields. Two field experiments were conducted in the summer of 2014 to determine the effectiveness of Fe chelate application in alleviating IDC in grain sorghum. Treatments in the first study were four Fe chelate application rates (0, 3, 6, and 9 lb/a) applied either in-furrow with the seed at the time of planting or 2 weeks after planting. A split treatment of 3 lb/a applied at planting and another 3 lb/a applied 2 weeks after planting was included. The second study was a split-plot design with two Fe chelate products as main plots and sorghum hybrids (Golden Acres 5613 and Sorghum Partners hybrid NK5418) as the subplot factor. Results showed IDC scores among the treatments were significant only in the early stages of growth. Severity of IDC tends to decrease throughout the growing season, confirming the ability of sorghum hybrids to grow out of IDC under favorable environmental conditions. Iron chelate application did improve sorghum yield, with the highest yield occurring when Fe chelate was split-applied at 6 lb/a. The two grain sorghum hybrids evaluated differed in their response to IDC and grain yield. GA5613 showed greater tolerance to IDC than NK5418. Application of Fe chelate to GA5613 had no effect on grain yield; however, Fe chelate application significantly improved grain yields in NK5418. Our preliminary findings suggest the first 30 days of growth may be the critical period to control IDC in grain sorghum.
Keywords: grain sorghum; iron deficiency; chlorosis; iron chelates